TRANSFORMATIVE LEADERSHIP AND ORGANIZATIONAL CULTURE EFFECT ON EMPLOYEE PERFORMANCE: EVIDENCE FROM THE INDONESIA LOGISTICS BUREAU - Astadi Pangarso; Romat Saragih; Waode Alaya Nuriz (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2021)
The purpose of this research was to analyze the effects of transformative leadership and organizational culture on employee performance in the context of the Indonesian Logistics Bureau. This study filled a research gap, and required repeated tests to assess the impact of transformative leadership and organizational culture on employee performance from different viewpoints. The research tool used was a cross-sectional quantitative study by a questionnaire (survey) of up to 69 respondents for all personnel of the Indonesia Logistics Bureau West Java Regional Division. Multiple linear regression analysis of data processing techniques revealed that the performance of employees was influenced by transformative leadership and organizational culture. The results of this analysis included positive guidance, in particular on the importance of a leader's role in empowering and encouraging workers through active engagement with them, and the presence of positive organization principles boosted organization performance.